Assessment of health literacy and self-care in heart failure patients - Hassan Sheikh Sharafi; Bayaneh Seyed amini (Mashhad University of Medical Sciences, 2017)
Background and objective: Self-care is one of the most important elements of life and success in the treatment of patients with heart failure; on the other hand health literacy is the first and most effective step on self-care, so the aim of this study was to investigate the relationship between health literacy level and self-care in patients with heart failure. Methods: This study with descriptive-correlation approach was done among 105 patients with heart failure who referred to Imam Khomeini hospital in Mahabad during1394-95 who were randomly selected. Data were collected by two standard questionnaires self-care of heart failure index (SCHFI V6.2) and Health Literacy for Iranian Adults (HELIA). Data, were analyzed by SPSS software and Pearson tests, chi- Square linear regression. Results: The average age of participants 12/81 ± 60/74 years. Health literacy levels according to the questionnaire HELIA, 6.91 per cent at the intermediate level, 28.6 percent was inadequate and 5.9 percent was favorable. In the area of self-care, respectively, maintaining self-care subscale with an average of 5.24 ± 21.37, self- confidence in self-care with 3.78 ± 15.39 and self-care management 4.18 ± 15.01 respectively. There was a significant relationship between general health literacy and three subscales of self-care and age, education and occupation (p <0/005). Statistical analysis showed a significant positive correlation between health literacy scale and self-care subscales (p <0/001). Conclusion: The dimension of assessment and access to health literacy were better predictors of self-care areas. With regard to the relationship between health literacy and areas of self-care in patients with heart failure, creating units in medical centers to identify factors associated with them to identify strengths and weaknesses in the way of self-care is recommended. Paper Type: Research Article.